Why Are University Endowments Large and Risky? - Gilbert, Thomas; Hrdlicka, Christopher (Review of Financial Studies, 2015)
We build a model of universities combining their real production decisions with their choice of endowment size and asset allocation. Variation in opportunity cost, that is, the productivity of internal projects, has a first-order effect on these choices. Adding the UPMIFA-mandated 7% payout constraint, the endowment size and asset allocations match those empirically observed. This constraint has little effect on universities that do not value the output of their internal projects but harms those that do: it prevents the endowment's use as an effective buffer stock, thereby increasing the volatility of production, and it slows the growth of the most productive universities.